1998
DOI: 10.1007/s003810050222
|View full text |Cite
|
Sign up to set email alerts
|

The ependyma in chronic hydrocephalus

Abstract: H-Tx rats produce congenitally hydrocephalic offspring with varying severity of the condition. We used moderately hydrocephalic rats without evident clinical signs of hydrocephalus and normal controls from the same stock when they were at least 1.5 years old. Macroscopic anatomy was studied by MRI and in fixed brain slices and the ultrastructure of the ependyma, with REM. Apart from markedly stretched areas, where the ependyma was totally destroyed and subependymal structures directly exposed to the CSF, the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0
3

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 14 publications
1
29
0
3
Order By: Relevance
“…Del Bigio et al 10 , Madhavi and Jacob 13 and Kiefer et al 11 have observed alterations on the choroid epithelium such as microvilii distortion, atypical cilia, fl atten cells with and vacuoles, intracellular inclusions and enlargement of intercellular space. Some of these alterations were also seen on the present study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Del Bigio et al 10 , Madhavi and Jacob 13 and Kiefer et al 11 have observed alterations on the choroid epithelium such as microvilii distortion, atypical cilia, fl atten cells with and vacuoles, intracellular inclusions and enlargement of intercellular space. Some of these alterations were also seen on the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The choroid plexus also present a role on the CSF clearance of drugs and substances formed on the brain tissue due to the metabolic reactions, thus presenting several active-transport systems 9,21 . The fi rst structure to suffer on the hydrocephalus process in high CSF pressure is the ependymal epithelium, with compression, distension and isolated disruption 10,11 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was suspected that the inheritance mode of LEW/ Jms changed over time (Jones et al, 2003). Both mutations were normally lethal at an early age, but a mild form of H-Tx rats was described (Kiefer et al, 1998). Yoon and Slaney (1972) described an autosomal recessive mutation in golden hamsters with a dome-shaped head.…”
Section: Discussionmentioning
confidence: 99%
“…Further, several possible ways to trigger chronic hydrocephalus from the obstruction of the cerebral aqueduct by cotton injection 5 , blood 6 , bacteries 7 , kaolin-aluminum silicate 8 , and others were described. The first structure that suffers because of the increase in CSF pressure and ventricular expansion is the ependyma, followed by the white matter 9,10 . Axonal degeneration and loss of myelin are observed in chronic hydrocephalus in the corpus callosum.…”
Section: Introductionmentioning
confidence: 99%